Dampak Modal Kerja Dalam Peningkatan Profitabilitas Pada Perusahaan Telekomunikasi - Maula, Sam Alpha; Tanuatmodjo, Heraeni; Purnamasari, Imas (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2018)
This study aims to determine the effect of working capital on profitability in telecommunications companies in Indonesia, namely PT. Indosat Tbk, PT. Smartfren Telecom Tbk, and PT. Bakrie Telecom Tbk 2006-2015. The type of research used is descriptive and verification. The sampling technique uses purposive sampling. Based on the results of the study indicate that there is a positive effect of working capital on profitability, which means that if there is a change in working capital it will affect the increase in profitability (ROA) of the telecommunications sub-sector. The difference in this research lies in the object of research, the time of the study, the measuring instrument, the literature used, the theory used and the results of the study.